The study of correlation of estrogen receptor, progesterone receptor, and HER2 receptor status in breast cancer and its incidence in a tertiary center hospital in south India - Shashikumar HB,; Sindhushree N,; Ramakrishna M,; Fathima Shihana Hameed, (Asian Journal of Medical Sciences, 2022)
Background: Breast cancer is the most common cancer in female representing approximately 25% of all cancer. It is also ranked number one cancer among Indian females with ageadjusted incidence rate of 25.8 per 100,000 women and mortality 12.7 per 100,000 women. Hormone receptors are the receptor protein found in normal breast cells. Aims and Objectives: The aims of this study were to assess the histologic type, estrogen receptor (ER), progesterone receptor (PR), and HER2/neu of all breast carcinoma patients coming to the inpatient department of general surgery of a tertiary care hospital. This study was conducted to assess the histologic type, ER, PR, and HER2/neu of all breast carcinoma patients coming to the outpatient department of general surgery of a tertiary care hospital. Materials and Methods: The present study is a prospective observational study conducted in the department of general surgery at KR Hospital for 1 year from December 2020 to November 2021. All patients who underwent modified radical mastectomy for breast carcinoma or core biopsy to start chemotherapy and hormone therapy before surgery were included in the study. They were subjected to histopathological examination and immunochemistry. Results: The most common age group, in which breast carcinoma was diagnosed, was 51–55 years. The most common type of breast carcinoma is invasive ductal carcinoma seen in 66% of the patients. Among the 100 patients IHC, ER positive was seen in 54% of the patients, PR positive was seen in 39% of the patients, and HER2neu-positive was seen in 31% of the patients. Most common was ER/PR+HER2neu – in 28% of the patients. Triple-negative hormonal status was seen in 23% of the patients. Conclusion: This single institutional study of 100 cases of breast cancer patients from South India suggest that mean age of breast cancer patient was between 51 and 55 years, with invasive ductal carcinoma being the most common histological type with ER positivity of 54% and PR positivity of 39% and triple-negative cancers of 23%, not grossly different from rest of the country but significantly lower than Western studies.